The sound of the perpetrator – thoughts on trauma and voice in Big Little Lies - Juliet Rogers (Law Text Culture, 2020)
Sound is as much part of the atmospheres of justice as is touch or image or even smell. Sound gets into the body and it leaves a mark. Sometimes that mark can be called violence, sometimes harm, and sometimes a crime. In this article I discuss how sound, as voice as well as the other nebulous sonic elements, such as grunts, shuffles and sighs, can leave a mark that can be called trauma. Using psychoanalysis I discuss theories of trauma as they intersect with experiences of sound in the courtroom as well as in fictional narratives. I examine the mark of trauma, as an experience of rape, as it appeared in the series Big Little Lies and I discuss how it can appear in the courtroom using psychoanalysis and the work of thinkers on sexual assault, on voice and on sound. I conclude that sound cannot not be part of the thinking on justice for victim-survivors of sexual assault, as well as of other interpersonal crimes.